Marching season, the - Silva, Daniel, 1960- (Michael Osborne, 2023)
An embittered ex-CIA agent, Michael Osbourne is drawn into the troubled peace of Northern Ireland when his father-in-law, ex-Senator Douglas Cannon, is appointed ambassador to Britain and becomes the target of ruthless assassin Jean-Paul Delaroche.